2015
DOI: 10.1155/2015/717926
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Health Insurance Status and the Pattern of Traditional Medicine Utilisation in Ghana

Abstract: This paper examines the relationship between national health insurance status and the pattern of traditional medicine (TRM) use among the general population in Ghana. A retrospective cross-sectional survey of randomly sampled adults, aged ≥18 years (N = 324), was conducted. The results indicate that TRM use was high with prevalence of over 86%. The study found no statistically significant association between national health insurance status and TRM utilisation (P > 0.05). Paradoxically, major sources of TRM, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
3
11
0
1
Order By: Relevance
“…The disappointing renewal rate could also be explained by the long waiting times and delays that subscribers have to tolerate to reinstate their NHIS membership. This finding concurs with the observation of Gyasi ( 2015 ), which indicated that the NHIS does not offer value for money in terms of the health and well-being of its card bearers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The disappointing renewal rate could also be explained by the long waiting times and delays that subscribers have to tolerate to reinstate their NHIS membership. This finding concurs with the observation of Gyasi ( 2015 ), which indicated that the NHIS does not offer value for money in terms of the health and well-being of its card bearers.…”
Section: Discussionsupporting
confidence: 91%
“…The conscious inclusion of informal workers such as female head porters into a nationwide health insurance scheme comes, perhaps, as no surprise considering that over 90% of Ghana’s workforce is in the informal economy (Heintz 2005 ). Again, the NHIS (designed as a replacement of a “cash-and-carry system”) is one of the social intervention schemes mitigating inequalities in healthcare (Gyasi 2015 ) because it seeks to make healthcare affordable and accessible. According to Mandersheid ( 2013 ), having health insurance is key to healthcare access.…”
Section: Introductionmentioning
confidence: 99%
“…The study found, across different programmes of study and all academic levels, a high prevalence of indigenous therapies utilisation, which is largely comparable with the findings of previous studies among university students in the low, middle and high income economies 18, 20, 21, 22. This is subject, partly to the readily availability of traditional medicines on the one hand, and the modernisation or formalisation of herbal therapies into the conventional health system,21, 23 leading to an increased trust in traditional medical practices. The blanket utilisation of TRM may have implications for the health of the individual students since a substantial proportion claimed to have ever used unconventional medical practices in combination with conventional therapies.…”
Section: Discussionsupporting
confidence: 87%
“…Use of traditional medicine was high amongst both insured and uninsured but had no association with insurance status. 66 Quality of care and proximity were two factors that influenced the choice of care provider. 67…”
Section: Service Deliverymentioning
confidence: 99%